The importance of Risk Management Assessment: A proposal of an Index for Listed Companies - Osmar Axel Cervantes-Cabrera; Guadalupe del Carmen Briano-Turrent (Universitas Syiah Kuala, 2018)
AbstractObjective – This study aims to construct an innovative index that integrates the most important qualitative elements of risk management for listed companies. Design/methodology – This research is exploratory, since the subject has been rarely addressed in Mexico, so we will review the international literature on risk management and propose an instrument for measuring and monitoring risk management. The index proposed in this study is composed by five sub-indexes or dimensions, consisting of nineteen constructs that are expressed in one hundred items or statements, measured through a Likert scale and un-weighted. Results – The integral risk management index proposed are related to five dimensions: architecture of risk, risk culture, risk guideline, risk assessment and business strategy. This framework constitutes a base for the implementation and conceptualization of the risk management, which harmonizes the regulations and methodologies of greater importance at the international level. Adherence to this framework complies with all international requirements and has the basis for an efficient administration in the 21st century. This study could be a reference for those responsible on the risk management decisions in Latin American listed firms.